RNomic identification and evaluation of npcTB_6715, a nonprotein- coding RNA gene as a potential biomarker for the detection of Mycobacterium tuberculosis - Kanniappan, Priyatharisni; Ahmed, Siti Aminah; Rajasekaram, Ganeswrie; Marimuthu, Citartan; Ewe, Seng Ch’ng; Li, Pin Lee; Raabe, Carsten A.; Rozhdestvensky, Timofey S.; Thean, Hock Tang (Foundation for Cellular and Molecular Medicine, 2017)
Technological advances in RNA biology greatly improved transcriptome profiling during the last two decades. Besides the discovery of many small RNAs (sRNA) that are involved in the physiological and pathophysiological regulation of various cellular circuits, it becomes evident that the corresponding RNA genes might also serve as potential biomarkers to monitor the progression of disease and treatment. sRNA gene candidate npcTB_6715 was previously identified via experimental RNomic (unpublished data), and we report its application as potential biomarker for the detection of Mycobacterium tuberculosis (MTB) in patient samples. For proof of principle, we developed a multiplex PCR assay and report its validation with 500 clinical cultures, positive for Mycobacteria. The analysis revealed 98.9% sensitivity, 96.1% specificity, positive and negative predictive values of 98.6% and 96.8%, respectively. These results underscore the diagnostic value of the sRNA gene as diagnostic marker for the specific detection of MTB in clinical samples. Its successful application and the general ease of PCR-based detection compared to standard bacterial culture techniques might be the first step towards ‘point-of-care’ diagnostics of Mycobacteria. To the best of our knowledge, this is the first time for the design of diagnostic applications based on sRNA genes, in Mycobacteria.